Optimization of a modification technique for reducing irreversible adsorption within synthetic resins - Tomohiro Kinoshita; Huan-Jung Fan; Takashi Kawakita; Eiji Furuya (Adsorption Science & Technology)
Synthetic resin adsorbents comprise agglomerated gel-type microparticles. Although the excellent adsorption capacities of resins are useful in adsorbing various organic substances, the adsorbed molecules cannot be completely desorbed. A majority of the irreversible adsorbed molecules can be attributed to slow mass transfer within microparticles of resins and it may lower the recovery efficiency of resins. This study focuses on reducing the irreversible adsorption that occurs within a resin (FPX-66) to improve the overall recovery efficiency of the adsorbate. In order to reduce the irreversible adsorption capacity of the resin, styrene monomer was polymerized in microparticles of the resin. Effects of polymerized styrene concentrations and multi-cycle polymerization on irreversible adsorption capacity of the resin were investigated. The experimental results indicated that using one cycle of polymerization with 30–40 vol% of styrene solution is the most effective modification process. The irreversible adsorption capacity could be lowered by half with the above process.